Assessment of Gene Expression of some Biofilm- Related Genes in Staphylococcus aureus under the Effect of Lactobacillus acidophiluspression of some biofilm-mediated genes in Staphylococcus aureus under lactobacillus acidophilus effect - Al-Khazraji, Shaymaa Fouad Rasheed; Abd Aburesha, Rasmiya (Iraqi Journal of Science, 2026)
A wide range of infections result from the Gram-positive pathogen Staphylococcus aureus. One key virulence factor of this bacterium is the capacity to develop biofilm. Antibiotics are ineffective in treating a majority of infections linked with biofilm formation in this opportunistic bacterium. The current study was conducted to estimate the influence of cell-free supernatant (CFS) of lactobacillus acidophilus on the expression level of some biofilm-association genes in clinical strains of S. aureus. The antibiotic susceptibility pattern against twenty antibiotics and quantitative assay for biofilm development were examined for all bacterial isolates. Moreover, the agar well diffusion method was followed to evaluate the impact of CFS on the growth of S.aureus. In addition, real-time PCR was utilized to determine the impact of CFS extract on the transcription level of the genes involved in forming S. aureus biofilms (fib , eno,sdrC ). In isolates constituting biofilm, a high percentage of antibiotic resistance was detected. The CFS exhibited an antimicrobial effect toward strong biofilm-forming isolates. In addition, the results of real-time PCR for the treatment group showed a drop in the expression degree of fib and sdrC genes compared to the control group; meanwhile, the eno gene displayed upregulation after treatment with CFS. In conclusion, biofilm construction is a key strategy that may participate in preventing antimicrobial agents from killing S. aureus, especially since all isolates were multidrug resistant with a high percentage of strong biofilm former. In addition, CFS of lactobacillus acidophilus affects the growth of S. aureus and biofilm formation by displaying downregulation for some mediating biofilm formation genes.